The influence of local community stakeholders in megaprojects: Rethinking their inclusiveness to improve project performance. Issue 8 (November 2017) - Di Maddaloni, Francesco; Davis, Kate
Abstract: This paper organizes and synthesizes different extant research streams through a systematic literature review to identify connections and major assumptions on the influence of stakeholders in major Public Infrastructure and Construction projects (PIC), at the local community level. Findings suggest that research on stakeholder management has focused strongly on those stakeholders able to control project resources, whilst the effect on the legitimate 'secondary stakeholders', such as the local community, remains widely unexplored. Due to the unavoidable impact of major PIC on both people and places, it is suggested that seeking local community opinions in the initiation phase of the project and monitoring the megaproject impact at the local level can help to improve project performance. The output provides scholars and practitioners with future research directions and practical implications for an inclusive stakeholder management approach in construction megaprojects. Highlights: Explores stakeholders in Public Infrastructure and Construction projects. A systematic literature review examining local community perceptions of 'megaprojects'. To improve decision making to minimize environmental and social impact.